Increasing Resistance of Coagulase-Negative Staphylococci in Total Hip Arthroplasty Infections: 278 THA-Revisions due to Infection Reported to the Norwegian Arthroplasty Register from 1993 to 2007 - Olav Lutro; Håkon Langvatn; Håvard Dale; Johannes Cornelis Schrama; Geir Hallan; Birgitte Espehaug; Haakon Sjursen; Lars B. Engesæter (Advances in Orthopedics)
We investigated bacterial findings from intraoperative tissue samples taken during revision due to infection after total hip arthroplasty (THA). The aim was to investigate whether the susceptibility patterns changed during the period from 1993 through 2007. Reported revisions due to infection in the Norwegian Arthroplasty Register (NAR) were identified, and 10 representative hospitals in Norway were visited. All relevant information on patients reported to the NAR for a revision due to infection, including bacteriological findings, was collected from the medical records. A total of 278 revision surgeries with bacterial growth in more than 2 samples were identified and included. Differences between three 5-year time periods were tested by the chi-square test for linear trend. The most frequent isolates were coagulase-negative staphylococci (CoNS) (41%, 113/278) and Staphylococcus aureus (19%, 53/278). The proportion of CoNS resistant to the methicillin-group increased from 57% (16/28) in the first period, 1993–1997, to 84% (52/62) in the last period, 2003–2007 (P = 0.003). There was also significant increase in resistance for CoNS to cotrimoxazole, quinolones, clindamycin, and macrolides. All S. aureus isolates were sensitive to both the methicillin-group and the aminoglycosides. For the other bacteria identified no changes in susceptibility patterns were found.